How does economic development and import dependency affect agricultural price protection? A pooled cross-country and time-series analysis for the wheat sector - Roland Herrmann (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
This article analyzes determinants of agricultural price protection for one important food, wheat, in a pooled cross-country and time-series analysis. For the aggregate sample it is shown that wheat price protection increases with a rising level of economic development and with a growing import dependency in wheat. Beyond this general pattern, the paper shows that the variation in wheat price protection can be significantly better explained if qualitative variables are introduced additionally into the model. For example, in Japan, in the Northern countries and during the commodity price boom (197 3-75), wheat price protection followed a specific pattern. Income elasticities and import-dependency elasticities of wheat price protection are computed for all countries in 1968-80, and additionally for various sub-regions and sub-periods.
Keywords: 330; Agrarprotektionismus; Weizenpreis